2005
DOI: 10.1128/jb.187.15.5214-5223.2005
|View full text |Cite
|
Sign up to set email alerts
|

Resistance ofNeisseria meningitidisto the Toxic Effects of Heme Iron and Other Hydrophobic Agents Requires Expression ofght

Abstract: Several genetic systems that allow the use of iron-protoporphyrin IX (heme) have been described for the pathogenic bacterium Neisseria meningitidis. However, many questions about the process of heme acquisition and utilization remain to be answered. To isolate and analyze unidentified genes that play a role in heme iron uptake and utilization, a Himar1 transposon mutant library was screened in N. meningitidis serogroup A strain IR4162. One locus identified by transposon mutagenesis conferred protection against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The ⌬ght mutant showed an increased sensitivity to heme (Fig. 1A), confirming the previously reported ght mutant phenotype of another N. meningitidis strain (23). Also, in contrast to the parental strain, the ⌬ght mutant was sensitive to vancomycin and showed a slightly increased sensitivity to tetracycline and chloramphenicol (Fig.…”
Section: Phenotype Of a Ght Mutantsupporting
confidence: 79%
See 2 more Smart Citations
“…The ⌬ght mutant showed an increased sensitivity to heme (Fig. 1A), confirming the previously reported ght mutant phenotype of another N. meningitidis strain (23). Also, in contrast to the parental strain, the ⌬ght mutant was sensitive to vancomycin and showed a slightly increased sensitivity to tetracycline and chloramphenicol (Fig.…”
Section: Phenotype Of a Ght Mutantsupporting
confidence: 79%
“…Inspection of the sequence of Ght showed that it contains an N-terminal hydrophobic segment, six tetratricopeptide repeat (TPR) domains, and a putative C4-type zinc finger or zinc-binding domain (Fig. 3A) (23). Previously, the N-terminal hydrophobic sequence was suggested to function as a periplasmic targeting signal (23).…”
Section: Phenotype Of a Ght Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of this is the N. meningitidis gene of hydrophobic agent tolerance, ght. The mutation of ght causes increased susceptibility to heme and other hydrophobic agents (91). A broad spectrum of Gram-negative bacteria have ght homologs, including the pathogens E. coli O157:H7, V. cholerae, B. pertussis, Pasteurella multocida, H. influenzae, Salmonella enterica serovar Typhimurium, and Coxiella burnetii (91).…”
Section: Mechanisms Of Bacterial Heme Tolerancementioning
confidence: 99%
“…The mutation of ght causes increased susceptibility to heme and other hydrophobic agents (91). A broad spectrum of Gram-negative bacteria have ght homologs, including the pathogens E. coli O157:H7, V. cholerae, B. pertussis, Pasteurella multocida, H. influenzae, Salmonella enterica serovar Typhimurium, and Coxiella burnetii (91). The mechanism for the increased sensitivity of the ght mutant to heme and other hydrophobic agents has yet to be elucidated; nonetheless, it is separate from the Mtr efflux system and PilQ (91).…”
Section: Mechanisms Of Bacterial Heme Tolerancementioning
confidence: 99%